Antecedents of Visiting Decisions on Artificial Travel Destinations: Millennial Generation Perspectives - Sukaris Sukaris (INNOVATION RESEARCH JOURNAL, 2020)
The purpose of this study was to determine the effect of tourist motivation, electronic word of mouthand destination image on the decision to visit the Gunung Mas Palace in Lamongan. The sample usesnon probability sampling method with a purposive sampling or random sampling procedure byselecting 106 visitors. The data analysis technique uses multiple linear regression. The results ofmultiple linear regression analysis prove that tourist motivation and destination image proved not tohave a significant effect partially on decisions leading to Gunung Mas Palace in Lamongan, whileelectronic word of mouth proved to have a partially significant influence on the decision to visit theGunung Mas Palace in Lamongan